A puzzling case of stress cardiomyopathy with persistent leukocytosis (Indian Journal of Case Reports, 2026)
Adult-onset Still’s disease (AOSD) is a rare autoinflammatory multisystem disorder with diverse clinical manifestations, making diagnosis challenging. It remains a diagnosis of exclusion and requires a high index of suspicion. We report a 42-year-old female presenting with fever, sore throat, arthralgia, and dyspnea on exertion. Laboratory evaluation revealed leukocytosis. Echocardiography showed a left ventricular ejection fraction of 45% with regional wall motion abnormalities, and an initial diagnosis of stress cardiomyopathy and acute coronary syndrome was made. After excluding infectious, autoimmune, and hematological causes, she fulfilled the Yamaguchi criteria for AOSD. The patient responded to pulse steroid therapy but experienced relapses requiring initiation of biologics. The absence of standardized international guidelines highlights the need for robust diagnostic tools to enable early recognition and reduce disease-related morbidity and mortality. AOSD is a diagnostic dilemma, but treatment is even more challenging.